Pintura, cultura e realidade (Revista Apotheke, 2019)
This article aims a reflection about art as knowledge area that studies and disseminates culture. Therefore, the scenarios of modernity and postmodernity suggest, as Lipovetsky (2004) presents, the advance of the production of subjectivity through culture and consumption systems. It influences the desires and the formation of individuals. For this reason, Guattari and Rolnik (1996) differentiate the processes of singularization (which intends to make individuals aware of the imposed subjectivities in order to create alternatives for an autonomous life) and individualization (this refers to the efforts of the capitalist production for regulate the groups according with consumption). In this sense, the ideas of Merleau- Ponty (2013) about the raw material of painting are exposed: culture and social relations in their respective contexts. Also through the texts of Sabino (2018) the role of painting is analyzed as a reading of reality. Painting and artistic work in this scenario can contribute to the identification of social realities as a new process of perceptions and sensibilities
Keywords: culture; painting; subjectivity; reality